Interpretation of radio afterglows in the framework of the standard fireball and energy injection models. Issue 3 (26th December 2022) - Levine, D; Dainotti, M; Fraija, N; Warren, D; Chandra, P; Lloyd-Ronning, N
ABSTRACT: Gamma-Ray Bursts (GRBs) are panchromatic, highly energetic transients whose energy emission mechanism is still debated. One of the possible explanations is the standard fireball model, which can be tested with the closure relations (CRs), or relations between the temporal and spectral indices of a GRB. To test these, we compile an extensive sample of radio afterglow light curves (LCs) that span from 1997 to 2020, the most comprehensive analysis of GRBs with radio observations to date. We fit 202 LCs from 82 distinct GRBs with a broken power law, obtaining a sample of 26 that display a clear break and a sub-sample of 14 GRBs that present a radio plateau. We test these samples against CRs corresponding to a constant-density interstellar medium (ISM) or a stellar wind medium in both fast- and slow-cooling regimes, as well as three additional density profiles, k = 1, 1.5, 2.5, following n ∝ r − k, and consider sets of CRs both with and without energy injection. We find that 12 of the 26 GRBs (46 per cent), of which 7/12 present a radio plateau, fulfill at least one CR in the sets tested, suggesting our data are largely incompatible with the standard fireball model. Of the fulfilled CRs, the most preferred environment is the ISM, SC, νm < ν < νc without energy injection. Our results are consistent with previous studies that test the standard fireball model via the CRs in radio.